Recent Perspectives and Upcoming Directions in Molecular Diagnosis of Malaria: A Systematic Review - Ola S. H. Almusaddar; Cyuzuzo Callixte (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Malaria remains a global leading cause of morbidity and mortality. The absence of effectivevaccines is still the vital hindrance to the management and elimination of malaria. From that standpoint,accurate laboratory diagnosis could be the right hand for disease management. Objective: This reviewintended to assess the recent perspectives and upcoming directions in molecular diagnosis of malaria.Methods: This review was conducted by using internet searching tools where 35 published papers wereretrieved from the credible online publishers and among them, 27 papers that satisfy the inclusion criteriawere profoundly reviewed.Results: Among the 27 articles, 22(81.48 %) papers focus on contribution of PCR based-method in malariadiagnosis, 4(14.8%) report on comparison between polymerase chain reaction(PCR) and other moleculartechniques, 7(30%) emphasize on advantages and disadvantages of PCR, 4(14.8%) represent relationshipamong PCR and LAMP, 3(11%) discuss the most promising molecular diagnostic tools, 5(18%) focus oncomparative designs of different PCR methods, whereas 1(3.7%) emphasizes on parasite density and 2(7%)on pigment containing monocyte.Conclusion: This review conclude that microscopy remains the gold standard method for malaria diagnosisand speciation in limited resource settings but also molecular based-methods provide significant alternativeswith superior sensitivity and specificity.